The Influence of Brand Awareness, Perceived Quality, Brand Association, Brand Loyalty on Brand Equity of Zakat Institutions - Muhammad, Doddy; Juhary, Ali; Anton, Hindarjo; Cicih, Ratnasih (2020)
This study aims to examine how the influence, among others, brand image, perceived quality, brand loyalty to brand equity in a zakat institution. The research design used is descriptive and explanatory with a quantitative approach. The sample size is 375zakat payers from a leading zakat institution in Greater Jakarta. The method of collecting data by distributing questionnaires was taken by clustered random sampling. Data processing used Partial Least Square SEM (PLS-SEM), where the results showed a significant influence between the variables of brand awareness, perceived quality, brand association, brand loyalty to brand equity. According to previous studies, brand loyalty has a dominant effect on brand equity as a whole. Zakat institutions must pay attention to the antecedents of brand equity in order to increase zakat fundraising.